Literasi Pengelolaan Keuangan Pribadi bagi Masyarakat Desa Jati Endah - Alwi, Fachri; Agustina, Lidya; Meythi, Meythi; Martusa, Riki (Universitas Nusantara PGRI Kediri, 2025)
The problem encountered in the Jati Endah Village community is the low level of financial management literacy which is indicated by the lack of public understanding regarding personal financial management. This community service activity aims to improve public understanding regarding personal financial management so that people are able to manage their finances optimally. The method of activity carried out is community service in the form of coaching including material presentation accompanied by financial management practices. The results of the community service show an increase in public understanding regarding how to manage personal finances and finances in the business being run. The community also understands the concepts and accounting equations in financial reports which are useful in future financial planning. This activity received a positive response and high enthusiasm from the participants so that it was considered to provide a positive contribution to the community. With the coaching activities carried out, it is hoped that the community can effectively manage their personal finances, be able to plan business development and achieve economic independence in a sustainable manner.